Regularity concepts in nonsmooth analysis : theory and applications - Bounkhel, Messaoud (Springer Optimization and Its Applications,, 2012)
Regularity concepts have played an increasingly important role in the applications of nonsmooth analysis, including differential inclusions, optimization, and variational inequalities. This heightened role has made it beneficial to introduce graduate students and young researchers to the basic concepts of regularity and their applications. This book is devoted to the study of various regularity notions in nonsmooth analysis and their applications. It is the first thorough study of the regularity of functions, sets, and multifunctions, as well as their applications to differential inclusions and variational inequalities.   Regularity Concepts in Nonsmooth Analysis is divided into three accessible parts. The first section presents a thorough introduction to nonsmooth analysis theory, using examples and exercises to explain main concepts and show useful results. The second part demonstrates the most recent results of various regularity concepts of sets, functions, and set-valued mappings in nonsmooth analysis. The final section addresses different applications, including first order and second order differential inclusions, quasi-variational, and equilibrium theory.   This book is designed for graduate students, researchers, and general practitioners interested in the applications of nonsmooth analysis.